Correlation between virulence and antimicrobial resistance to antimicrobial drugs in Klebsiella Pneumoniae - Nusrat Bibi; Sabahat; Zahra Kalim; Muhammad Owais; Hafiz Ali Raza; Shaheen Kausar (AMMANIF, 2023)
Klebsiella pneumoniae is accountable for a widespread range of infections such as pneumonia, urinary tract infections, liver abscesses and bacteremia. In addition to susceptible clinical isolates involved in multidrug-resistant (MDR), nosocomial infections and hypervirulent (hvKP) strains have evolved separately in distinct clonal groups. These isolates are spread in various geographical regions globally. However, the virulence of K. pneumoniae is still unknown but the virulence of hvKP is beginning to revealed. The antimicrobial resistance is creating threatened for the treatment of K. pneumoniae. The antimicrobial resistance is usually associated with genetic mobile elements such as plasmids having virulence determinants. A proficient pathogen should be virulent, resistant to antibiotics, and epidemic. However, the interplay between resistance and virulence is poorly understood. Here, we review current knowledge on the topic.